2022
DOI: 10.1007/s00167-022-07169-y
|View full text |Cite
|
Sign up to set email alerts
|

Deltoid ligament (DL) repair produced better results than DL nonrepair for the treatment for rotational ankle instability

Abstract: Purpose To compare the clinical and magnetic resonance imaging (MRI) results after arthroscopic deltoid ligament (DL) repair versus DL nonrepair in patients with rotational ankle instability. Methods All patients with rotational ankle instability were enrolled in this retrospective cohort study. Clinical evaluation was performed by the American Orthopedic Foot and Ankle Society (AOFAS) score, Karlsson Ankle Functional Score (KAFS), and Tegner activity score preoperatively and at a minimum follow-up of 2 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although recent studies showed no differences in long term functional outcomes when the deltoid ligament was repaired (13), the deltoid ligament repair may lead to better ankle stability (11,14). Thus, more and more researchers believe that surgical repair of deltoid ligament rupture is the first choice to maintain the stability of ankle joint and prevent the occurrence of valgus and extransion of talus and long-term traumatic arthritis (15)(16)(17). In the present study, good functional outcomes were achieved and technique safety was observed based on the results of AOFAS, VAS, and ankle ROM.…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies showed no differences in long term functional outcomes when the deltoid ligament was repaired (13), the deltoid ligament repair may lead to better ankle stability (11,14). Thus, more and more researchers believe that surgical repair of deltoid ligament rupture is the first choice to maintain the stability of ankle joint and prevent the occurrence of valgus and extransion of talus and long-term traumatic arthritis (15)(16)(17). In the present study, good functional outcomes were achieved and technique safety was observed based on the results of AOFAS, VAS, and ankle ROM.…”
Section: Discussionmentioning
confidence: 99%
“…A similar lack of consensus exists on the best strategy for treating DL injuries. Vega et al introduced a surgical technique for repairing the anterior fibers of the deltoid ligament using a single anchor and non-absorbable sutures ( Vega et al, 2020 ), and Li et al detailed a method for repairing the deep fibers in the DL using a similar approach ( Li et al, 2023 ). Higashiyama et al used autologous tendon grafts for anterior tibiotalar ligament (ATTL) reconstruction ( Higashiyama et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%